2011
DOI: 10.3109/10253890.2010.545458
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced salivary cortisol secretion during hypobaric hypoxia challenge andin vivourinary thromboxane production in healthy male subjects

Abstract: Few studies have assessed the effects of stress on in vivo platelet activation. In the present study, hypobaric hypoxia induced by rapid decompression during high-altitude simulated flight in a hypobaric chamber was used to evaluate the effects of environmental stress on salivary cortisol and urinary thromboxane metabolite (TXM) excretion, a noninvasive marker of in vivo platelet function. Twenty-one male aviators (mean ± SD age = 36 ± 7 years) experiencing hypoxia by removing their oxygen mask for 4-5 min dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Researchers studied salivary cortisol (11,28,3034,37 40 ,42 47,4954,5668,70,71) and/or salivary α-amylase response to stress (11,29,32,33,35,36,40–42 ,44 ,48,49,52,53,55,59 ,61,63,66,6972) for their association with CV/CM items. A substantial number of these studies showed significant correlations between salivary cortisol and/or salivary α-amylase and clinical/subclinical CV/CMR indicators (28,29,31,32,36,37,44,50,55).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers studied salivary cortisol (11,28,3034,37 40 ,42 47,4954,5668,70,71) and/or salivary α-amylase response to stress (11,29,32,33,35,36,40–42 ,44 ,48,49,52,53,55,59 ,61,63,66,6972) for their association with CV/CM items. A substantial number of these studies showed significant correlations between salivary cortisol and/or salivary α-amylase and clinical/subclinical CV/CMR indicators (28,29,31,32,36,37,44,50,55).…”
Section: Resultsmentioning
confidence: 99%
“…A substantial number of these studies showed significant correlations between salivary cortisol and/or salivary α-amylase and clinical/subclinical CV/CMR indicators (28,29,31,32,36,37,44,50,55). Several studies have demonstrated the association between stress-induced salivary cortisol and/or salivary α-amylase modifications and CV/CMR clinical/subclinical indicators (11,35,47,70,71).…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of salivary cortisol, sAA and DHEA is becoming more widely accepted for monitoring changes in HPA and SAM activity under stress-related conditions [35,36,48,49,57]. Changes in salivary cortisol, sAA and DHEA levels, as well as their diurnal fluctuations, are thought to have implications for health [1,70,8].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio between the two steroids ( Fig. 2 , right) was quantifi ed, and no statistically signifi cant differences were observed between the cortisol-to-DHEA-S ratios measured on the day of the hypobaric chamber experience and those measured in the no-stress condition (F (2,22) 5 0.251; P 5 0.780).…”
Section: Salivary Dhea-smentioning
confidence: 93%
“…Coste et al ( 2 ) suggested that prolonged mild hypoxia altered the expression of the cortisol circadian rhythm. More recently, we were able to show that hypobaric hypoxia induced a large reversible increase in salivary cortisol, with no alteration of the physiological diurnal fl uctuation ( 22 ). These discrepancies prompted us to evaluate in depth the effect of barometric pressure decrease on HPA activity.…”
mentioning
confidence: 97%